Todd Solondz - Murphet, Julian (Contemporary film directors., 2019)
"Films like Welcome to the dollhouse and Happiness established Todd Solondz as independent cinema's premier satirist. Blending a trademark black humor into atmospheres of grueling bleakness, Solondz repeatedly takes moviegoers into a bland suburban junk space peopled by the damaged, the neglected, and the depraved. Julian Murphet appraises the career of the controversial, if increasingly ignored, indie film auteur. Through close readings and a discussion with the director, Murphet dissects how Solondz's themes and techniques serve stories laden with hot-button topics like pedophilia, rape, and family and systemic cruelty. Solondz's uncompromising return to the same motifs, stylistic choices, and characters rejects any idea of aesthetic progression. Instead, he embraces an art of diminishing returns that satirizes the laws of valuation sustaining what we call cinema."